Improved Direct-Model Predictive Control with a Simple Disturbance Observer for DFIGs - Abdelrahem, Mohamed; Hackl, Christoph; Rodriguez, Jose; Kennel, Ralph (2020 22nd European Conference on Power Electronics and Applications (EPE'20 ECCE Europe), 2020)
In this paper, a computationally-efficient and robust direct-model predictive control (DMPC) technique for doubly-fed induction generators in variable-speed wind turbines systems is proposed. In order to avoid several predictions of the rotor currents, the reference voltage (RV) is directly computed from the reference currents, which notably reduces the calculation load. Furthermore, the disturbances due to parameters mismatches and un-modeled dynamics are considered in the RV calculation. Accordingly, the sensitivity to mismatches in the model parameters is avoided and a zero steady-state error is realized. Finally, based on the location of this RV, the quality function is evaluated for only two times to find the best switching state, which is applied to the power converter in the next sample. The performance of the suggested DMPC is experimentally validated and compared with the convention DMPC.